Simulation of real investment by options method - Taikulakova, G.S.; Alibekova , D. (BUKETOV BUSINESS REVIEW, 2017)
According to economic studies was found that the real options method can improve the substantiation of investment projects, which are characterized by strong uncertainty of parameters and conditions of sale. This method provides an account of the latent possibilities of such projects and their formation so that each initially contained the largest possible number of real options. These options provide the basis for developing managers flexibility in the implementation of the project and increase the chances of success of its implementation.Based on the methods of stochastic analysis can develop a model for the evaluation of investment projects in the conditions of high uncertainty, as the valuation of the option to the cash flows of the project, which is reduced to a factor of market stability while reducing the level of uncertainty. This model includes such factors as the value of the option on the investment, the critical level of cash flow, the critical value of the investment, the critical level of uncertainty and the attractiveness of the business rate. This article talks about the real options method like, more effective method of valuation of investment projects. Particularly, the article gives the definition of real options, their classification and considers the main imperfections of traditional discounted cash flow method of valuation of investment projects. In addition, article discusses the perspectives of using the Black-Scholes model in the future by example.